Does Good Governance Practice Leads to Sound Financial Performance? Evidence from RMG Companies Enlisted in Dhaka Stock Exchange (DSE) - Hossain, S. M Khaled; Akib, Jobaer Hossan; Anannya, Anjuman (International Journal of Management and Sustainability, 2020)
The purpose of the study is to investigate the impact of good governance on financial performance as well as internal and external financial performance. The population of the study consists of 56 readymade garments companies enlisted in Dhaka Stock Exchange. 40 companies of the total population were conveniently selected as sample size for conducting the research. The data used in the study was collected from basically secondary source mainly extracted from the annual reports of the sampled companies during the study period of 2019. For performing the data analysis, rigorous econometric tools such as descriptive statistics, normality statistics, correlation test, multiple OLS regression analysis were used with the support of SPSS software (Version-23.0). The results of the study found that, companies’ board structure, ownership structure and audit committee structure have significant impact on ROA used as proxy of internal financial performance and MBR used as a proxy of external financial performance. The study also found positive impact of firm specific control variable firm size on financial performance whereas institutional ownership affects financial performance of the studied companies inversely.